Efeito de temperaturas alternadas sobre desenvolvimento de Aedes (Stegomyia) aegyoti (L.) (Diptera: Culicidae) - Paiva, Fernando Henrique de Sá [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
Aedes (Stegomyia) aegypti is a species of mosquitoes known to be the vector of diseases such as dengue and yellow fever, and a better understanding of aspects of their biology can help in the establishment of control strategies for the same. Several previous studies showed that temperature significantly affects the development of immature stages of insects. In general, higher temperatures (up to a threshold) accelerate the development of insects, and lower temperature retards the same. This rule also applies to mosquitoes, including Ae. aegypti. But not still know the effects of daily variation of temperature on the developmental stages of mosquitoes. And this detail is very important, since in natural breeding or artificial, The mosquitoes usually face temperature variations over a single day, which should interfere with its development until the emergence of the adult forms. For this reason, the objective of this study is to analyze the effect of alternating temperatures on the development of Ae. aegypti. To conduct the study, adults were collected active in the neighborhood Bela Vista Campus of UNESP - Rio Claro, SP, using a sweep net or using ovitraps for immatures, and the active search for breeding. Individuals collected were kept under experimental conditions in the laboratory. The adult samples were identified to species level, were considered for the experiments, only samples of Ae. aegypti. The insects were housed in plastic cages, suitable for creating flies. These were fed with sugar solution and blood meal on alternate days. The eggs obtained were used in the experiment with four different temperature regimes. The data collected were analyzed by evaluating whether the different treatments influenced the development of immature to adult, performing the Kruskal-Wallis test and the statistical software BioEstat. Statistical analysis of the sex ratio... (Complete abstract click electronic access below)

Aedes (Stegomyia) aegypti é uma espécie de culicídeo conhecida por ser vetora de doenças, como dengue e febre amarela, e o melhor conhecimento de aspectos de sua biologia pode auxiliar no estabelecimento de estratégias de controle para a mesma. São vários os estudos já realizados que mostram que a temperatura interfere significativamente no desenvolvimento dos estágios imaturos de insetos. De uma forma geral, temperaturas mais altas (até certo limiar) aceleram o desenvolvimento dos insetos, e temperaturas mais baixas retardam o mesmo. Esta regra aplica-se também aos culicídeos, dentre eles o Ae. aegypti. Porém, ainda não se conhecem os efeitos da variação diária da temperatura sobre os estágios de desenvolvimento de mosquitos. E este detalhe é muito importante, já que em criadouros naturais ou artificiais, os culicídeos normalmente enfrentam variações de temperatura ambiente ao longo de um único dia, o que deve interferir em seu desenvolvimento até a emergência das formas adultas. Por este motivo, o objetivo do presente estudo é analisar o efeito de temperaturas alternadas sobre o desenvolvimento de Ae. aegypti. Para a realização do trabalho foram feitas coletas ativas de adultos no Campus do bairro Belas Vista da UNESP – Rio Claro, SP, utilizando uma rede entomológica ou de imaturos utilizando ovitrampas, além da busca ativa por criadouros. Os indivíduos coletados foram mantidos sob condições experimentais em laboratório. Os exemplares adultos foram identificados até o nível de espécie, sendo considerados para os experimentos, apenas exemplares de Ae. aegypti. Os insetos foram abrigados em gaiolas plásticas, próprias para criação de dípteros. Estes foram alimentados com solução açucarada e o repasto sanguíneo em dias alternados. Os ovos obtidos foram utilizados no experimento com quatro diferentes regimes de temperatura... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Aedes aegypti; Mosquito; Termobiologia; Temperatura; Inseto